Adjuvant therapy for cutaneous melanoma: a systematic review and network meta‐analysis of new therapies. (6th January 2020) - Longo, C.; Pampena, R.; Lallas, A.; Kyrgidis, A.; Stratigos, A.; Peris, K.; Garbe, C.; Pellacani, G.
Abstract: New drugs have been recently approved as adjuvant therapies for melanoma. In this Bayesian network meta‐analysis, we aimed to assess the best therapeutic option in terms of recurrence‐free survival (RFS), overall survival (OS) and adverse events (AEs). PubMed, Embase, Cochrane library and the American Society of Clinical Oncology databases were searched from inception until 20 August 2018. We estimated adjusted hazard ratios (HRs) for RFS and OS and relative odds ratios (ORs) for AEs and surface under the cumulative ranking (SUCRA) probabilities were calculated. A number of 872 records were identified, and six were finally included in the meta‐analysis. A total of 4244 patients in six studies were randomized. The following therapies were considered in the selected studies: combined dabrafenib and trametinib, vemurafenib, nivolumab, ipilimumab and pembrolizumab. Nivolumab demonstrated the highest probability (75.1%) of being the best in term of RFS, followed by dabrafenib+trametinib, pembrolizumab, ipilimumab and vemurafenib; however, OS was not estimable. Concerning AEs, pembrolizumab and nivolumab showed the highest probability to be less associated with any and 3–4 grade AEs (83.1% and 64.4%, respectively). In conclusion, all new drugs are highly effective in adjuvant setting, and the best choice is dependent of patient's context.